THE INFLUENCE OF SOCIAL MEDIA PROMOTION ON NON-AERONAUTICAL REVENUE AT MINANGKABAU PADANG INTERNATIONAL AIRPORT - Harum Kinanti, Sekar; Puspita Ningsih, Ramining; Driyono, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Social media plays a crucial role in promotional efforts to support the increase of non-aeronautical revenue, particularly in the food and beverage sector. This study aims to examine the influence of social media promotion on non-aeronautical revenue at Minangkabau International Airport Padang, with a specific focus on the food and beverage sector. Data were collected using a descriptive quantitative method through questionnaires distributed to 30 respondents. Data analysis involved several statistical tests, including validity, reliability, normality, t-test, and Spearman correlation tests. The results indicate a positive and significant influence, as evidenced by a t value of 11.165, which is greater than the t table value of 2.045, and a significance level of 0.000 < 0.05. Additionally, the Spearman correlation test showed a very strong relationship between the two variables, with a correlation coefficient of 0.904. These findings affirm that optimizing social media usage can significantly contribute to increasing non-aeronautical revenue at the airport. Result the study recommends a more targeted and collaborative digital promotion strategy between airport management and tenants to maximize non-aeronautical revenue potential.